The Connection Between Heritage And Modernity - maazouzk, khaira (El Omda in Linguistics and Discourse Analysis, 2024)
The foundation upon which humanity has been based since the first eras to this day is communication, whether linguistic or otherwise, through signs, gestures and symbols, and their realization. The interest among Arabs and Muslims was paralleled by their interest in the Arabic language at all levels, so they wrote valuable books in which our authentic heritage was mocked, such as the book of Al-Bayan and Al-Tebeen by Al-Jahiz.And the writer's literature for Al-Mubarrad and the evidence of the inimitability of Al-Jarjani ... Therefore, the following problem was formed. Where is the contact in the Arab heritage? Is it possible to root for an Arab theory? Accordingly, the researchers worked on heritage with the aim of revealing it by applying the latest methods in analysis and understanding and attaching it to modernity and contemporary in the hope of authentic Arab perceptions, especially since communication theories crystallized in the West